Teaching Style and Performance of The Faculty of a Technical School in Cebu City - Narsico, Lalaine O.; Narsico, Peter G.; Polinar, Mark Anthony N. (Future Science / FSH-PH Publications, 2023)
Educators should use different teaching methods to engage students in meaningful learning experiences and promote environmental awareness. This study sought to assess the manifestation of teaching styles and teaching performance in a technical school and identify areas for enhancement. Utilizing a descriptive survey method, teachers, students, and administrators were asked to complete questionnaires to provide data for the study. The results indicated that teaching styles and teaching performance components were highly rated, with teaching styles being frequently observed and teaching performance being excellent. Notably, there was no significant difference in responses from the three groups surveyed. To facilitate further improvement, the technical school is encouraged to identify relevant components for their specific context, establish core principles for each component, organize regular workshops and seminars, periodically evaluate performance to monitor progress and establish mechanisms for continuous development.